Perceptions and Responses of Prospective Biology Teachers on The Use of Virtual Laboratories in Learning Plant Tissue Biology Material - Habibatul Unayah; M.Rasyid Nur Khilafah; Ngade Wantara (Proceeding International Conference on Religion, Science and Education, 2023)
This study aims to examine the perceptions and responses of prospective biology teachers towards the use of virtual laboratories in teaching plant tissue material. This research involved prospective biology teachers, namely biology education students from universities in Indonesia. Students answered 15 questionnaire questions which were distributed online. Questionnaire result data will be analyzed quantitatively and qualitatively. This study shows the results that prospective biology teacher students have positive perceptions and responses to the use of plant tissue virtual laboratories in biology learning. Biology teacher candidate students strongly agree that the plant tissue virtual laboratory is easier to use in terms of accessing and displaying microscopic visual images of plant tissue. Responses from biology teacher candidate students indicate that they agree to use the plant tissue virtual laboratory as a biology learning medium. The use of a plant tissue virtual laboratory also has the potential to increase student motivation and learning outcomes in learning plant tissue biology material.